KONFLIK AGRARIA DI KECAMATAN SEMBALUN KABUPATEN LOMBOK TIMUR NUSA TENGGARA BARAT 1979–2019 - Umaruddin, Dani (Jurnal Ilmiah Widya Sosiopolitika, 2021)
ABSTRACT This study discusses agrarian conflicts that occurred in Sembalun District, East Lombok Regency, West Nusa Tenggara from 1979–2019. The problems in this study are: 1) Why are there agrarian conflicts in Sembalun District? 2) What are the forms of agrarian conflict that occurred in Sembalun District? The method used is the Critical Historical Method. Meanwhile, the theory used is Historical Dialectical Materialism from Karl Marx and Conflict theory from Ralf Dahrendorf. The results of this study indicate that the agrarian conflict in Sembalun District in 1979–2019 was a structural agrarian conflict. It takes the form of conflicting claims between the Sembalun indigenous peoples and the government and companies regarding who has the right to access land and natural resources. The main cause of the conflict is the lack of community land that becomes their means of production to meet their material subsistence needs. This is due to the practice of negarasasi (land acquisition) carried out by the government and negating the customary law system in agrarian management in Sembalun. Conflict becomes less powerful when the massive Sembalun peasant community defends their land, and tries to restore the customary law system or what is called negation over negation. Keywords: Agrarian Conflict, Sembalun Society, Historical Dialectical Materialism.